2014 International Telecommunications Symposium (ITS) 2014
DOI: 10.1109/its.2014.6947975
|View full text |Cite
|
Sign up to set email alerts
|

Bufferbloat systematic analysis

Abstract: There is a recent interest in the bufferbloat phenomenon as a possible explanation for the increased network latency observed in the Internet. The bufferbloat phenomenon is related to the excessive packet queuing in over-sized buffers inside the network that may lead to network performance degradation. In this context, we observe a lack of experimental results considering the practical aspects of off-the-shelf network devices. Therefore, in this paper, we present a systematic analysis of the bufferbloat phenom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…In a systemic evaluation of the bufferbloat effect, Cardozo et al [8] suggested that bufferbloat might not be a significant problem in practice. Considering the microscopic view of the buffer architecture of typical network devices, they drew attention to the impact of varying the buffer size of various buffers in the network transmit stack.…”
Section: B Bufferbloatmentioning
confidence: 99%
“…In a systemic evaluation of the bufferbloat effect, Cardozo et al [8] suggested that bufferbloat might not be a significant problem in practice. Considering the microscopic view of the buffer architecture of typical network devices, they drew attention to the impact of varying the buffer size of various buffers in the network transmit stack.…”
Section: B Bufferbloatmentioning
confidence: 99%
“…Based on their work, [30] tried to capture this delay type and measure its significance by passively monitoring BitTorrent traffic. [31] analyzed bufferbloat in a testbed with typical network device buffer architecture. Although research results typically suggest that the extent of bufferbloat is not so significant, the question is still open and it remains an actively researched area (e.g.…”
Section: Related Workmentioning
confidence: 99%
“…In our previous work [4], we have presented a systematic analysis of bufferbloat considering a microscopic view of the buffer architecture of typical network devices. We have varied the sizes of two main network queues on Unix-based systems and we have notice the bufferbloat phenomenon only in specific cases.…”
Section: Bufferbloat Recent Solutionsmentioning
confidence: 99%
“…We are particularly interested in the system behavior while we vary qdisc and ring buffer queue sizes. 4 These queues store packets in the network and link layers, respectively. Further, we focus our analysis on the output from the ring buffer and qdisc queues since their input queues commonly present sufficient packet processing capacity.…”
Section: B Queue Configurationmentioning
confidence: 99%
See 1 more Smart Citation